Creative ways to memorize the Holy Quran - Sakr, Mohammed Ebrahim (Journal of Islamic Sciences, 2022)
This research aims to show the creative ways to memorize the Holy Qur’an; By clarifying the meaning and concept of creativity, clarifying the concept of memorizing and memorizing the Holy Qur’an, and displaying creative ways to memorize the Holy Qur’an These include: reciting the Noble Qur’an with recitation and improvement, concentration, with comprehensive understanding of the verses, and repetition of the verses until they are memorized. In this study, I relied on: the inductive method, and on the analytical method represented in presenting what was written about the creative methods of memorizing the Holy Qur’an, analyzing these methods and benefiting from them. Among the results of this research: that reciting the Qur’an with Tajweed is one of the ways that proves memorization in a stronger and broader way. Creative ways a comprehensive understanding of the Holy Quran leads to integrated memorization; It is understanding the meaning of the verses in such a way that it leads to the coherence of the meaning.